Ciudadanía y territorio: Escenario para la formación ciudadana (2009)
ABSTRACT: Democracy has become the most possible and desirable option to achieve the general welfare and improve quality of life of a population geographically located; to achieve it, it is necessary to get the actors and the active forces related to the process which leads to those goals. To make this democracy possible, it is required citizens willing to assume citizenship and to positively transform their reality. This kind of citizens is not born, they are made and they are grown rooted to their territory. Achieving this kind of citizens requires, among other things, conscious processes, through the education system, that allows those involved in the process to know, understand and put into practice the citizenship education potential as a pedagogical strategy to conceive them, promote citizenship and strengthen democracy. Thus, citizenship, territory and citizenship education arise as support for building democracy.